Papuan Rivalry and Harmony in Indonesia; Papua Student Racism Case in Surabaya City - Ulafirita, Ester S; Rusmanto, Joni; Sani, Yosafat (Jurnal Mamangan, 2023)
Rivalry and harmony always go hand in hand, moreover as a marker for a group of children of the nation that we can call the existence of Papua who are sometimes treated discriminatory in their own country. Rivalry and harmony in Papua in the context of the Unitary State of the Republic of Indonesia is a serious problem, then it has the potential to pose a threat to social disparity and even national disintegration. The emergence of humanitarian incidents was motivated by the existence of discriminatory issues both carried out by fellow children of the nation themselves, as well as the civil apparatus of the state which should legally protect all children of the nation without exception. This research discusses cases of racism against Papuan students who live temporarily to carry out studies in the city of Surabaya, East Java in 2019. Therefore, this study uses a case approach from a phenomenological perspective. Phenomenological study is a thinking methodology (tools), the construction of ideas in viewing, understanding a phenomenon in an event in various experiences of subjectivity that is experienced by the subject himself, giving meaning and meaning to an event in the dynamics of everyday life (everyday life). Conclusion of the discussion states that ideology often appears spontaneously because it has penetrated into the joints of people's lives.